Literacy and the bilingual learner texts and practices in london schools - Wallace, Catherine; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2013)
Literacy and the Bilingual Learner explores the literacy development of bilingual learners in London (UK) schools and colleges through a series of vignettes and case studies of learners and their educational experiences.
Keywords: Popular Works; Sociolinguistics; Literacy; Language and languages -- Study and teaching; Education; Popular Science; Popular Science in Education; Language Teaching; Sociolinguistics; Literacy